2002
DOI: 10.1111/1468-2427.00396
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of small transnational enterprise in Vancouver: the case of Chinese entrepreneur immigrants

Abstract: This article examines the small transnational enterprises of recent Chinese entrepreneur immigrants to Vancouver, Canada. These enterprises are part of the globalization process and contribute to the economic and cultural integration of certain regions of Asia with large urban areas of Canada. The entrepreneurs are analyzed utilizing a transnationalism framework which is situated in the ethnic enterprise literature. The article explains how these transnational small Chinese businesses are different from the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 7 publications
2
60
0
2
Order By: Relevance
“…Prior research has shown that entrepreneurs' transnationalism has resulted in new forms of cosmopolitan identity, which is still foreign in nature when compared to host countries' identities (Wong and Ng 2002). Thus, it is a worthwhile endeavor to empirically reexamine the older notions of foreignness in light of the contemporary transnationalism pressures (Kloosterman and Rath 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that entrepreneurs' transnationalism has resulted in new forms of cosmopolitan identity, which is still foreign in nature when compared to host countries' identities (Wong and Ng 2002). Thus, it is a worthwhile endeavor to empirically reexamine the older notions of foreignness in light of the contemporary transnationalism pressures (Kloosterman and Rath 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These transnational networks can be seen as an enhanced form of social capital potentially providing ethnic minority entrepreneurs with access to a flow of resources, new market opportunities and business ideas (Bagwell 2008;Portes et al 1999;Wong and Ng 2002). This 'diversity dividend', it is argued, can be used by otherwise disadvantaged ethnic minority entrepreneurs to gain a competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars such as Granovetter (1990) and Min and Bozorgmehr (2003); Wong and Ng (2000) and Sensenbrenner (1993), observed that, in order to sustain and maintain these two kinds of relationships, solidarity must be built between the two partners. This will go a long way to help the transnational entrepreneurs to utilise certain sanctions to enforce trust among them to keep the relationship moving all the time.…”
Section: Social Relations In Small-scale Enterprises and Entrepreneurmentioning
confidence: 99%